Age-Related Differences in Russian and Hungarian Linguistic Pictures of the World - Istvan Lenart; Irina Markovina; Orsolya Endrody (Journal of Eurasian Studies)
This cross-cultural, interdisciplinary study aims to investigate how the linguistic picture of the world differs in various age groups from kindergarten years to adulthood. In this paper, linguistic picture of the world is referred to as a technical term introduced into linguistics by Leo Weisgerber (Weltbild der Sprache). In order to trace the differences in Russian and Hungarian language users’ linguistic picture of the world in different age groups, thus obtaining a more precise picture of the linguistic development of the individual from a cross-cultural perspective, a research was conducted and data were collected with the aid of the association experiment, a foundational research method of Russian psycholinguistics. Respondents from three age groups (4–5 years, 10–12 years, and 18–26 years) were investigated via the collection of word associations to 10 stimulus words. As the research results suggest, culturally bound traits of linguistic development were identified, including the Russian linguistic consciousness changing its orientation from being self- and family-oriented in early childhood to being people-oriented (man-oriented) as an adult. The study also revealed common characteristics of the age-related development of the Russian and Hungarian linguistic pictures of the world, for instance, toys and games moving from the center of the linguistic image of the world to the periphery to be replaced by love . Results can be utilized not only for theoretical psycholinguistic purposes including a better description of the presumed age-related changes in the mental lexicon but also in the practical realm of education for curriculum development or the fine-tuning of pedagogical methods, as well as in intercultural studies for gaining a more precise picture of the linguistic consciousness of representatives of different cultures.